Diversity, Abundance, and Foraging Behaviour of Insect Pollinators in Litchi (Litchi chinensis Sonn.) under Hot and Subhumid Conditions - Pooja Kumari; Jaipal Singh Choudhary; Debjani Dey; Mahesh Kumar Dhakar (Psyche: A Journal of Entomology)
Insect pollinators and flowering plants have a long-standing, coevolutionary, mutualistic relationship. One such example is the litchi tree (Litchi chinensis Sonn.), a fruit crop that relies on insect pollination. Litchi flowers are hermaphroditic, but they cannot self-pollinate due to self-sterility, unlike self-pollinating plants. Therefore, insect pollinators are crucial to successful fruit development. To understand the pollinator’s foraging behaviour and diversity associated with litchi under hot and subhumid conditions, the present study was conducted on the Shahi variety of litchi at the ICAR-Research Complex for Eastern Region, Farming System Research Centre for Hill and Plateau, Ranchi (Jharkhand), India. During the flowering period, a total of 19 species of insect pollinators from the orders Hymenoptera, Diptera, Lepidoptera, and Coleoptera were observed visiting litchi inflorescences. Apis mellifera and Apis dorsata were the most dominant pollinator species. Each species displayed distinct characteristics in terms of abundance and diversity. Varied foraging speeds (stay times) were also noted, with A. dorsata (6.94 s) being the fastest and Musca domestica (2.88 s) being the slowest. Pollinator activity was highest in the eastern direction, between 8:00 a.m. and 10:00 a.m. Apis florea had the highest foraging rate (visitation rate) (14.02 flowers visited per minute), followed by Apis mellifera, while Episyrphus taeniops​ had the lowest. Apis species were identified as the most abundant and frequent visitors in litchi orchards.